Inventarisasi Sarana dan Prasarana Di MTs. Negeri 2 Jember - Purnamasari, Intan; Nafisah, Karunia; Dzakiri, Labib Hanif; Deesaeh, Khairul Anwar; Hidayat, Rofiq (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2025)
Educational asset management includes an inventory of facilities and infrastructure that play an important role in supporting the smooth teaching and learning process. This study aims to identify the actual condition of facilities and infrastructure at MTs. Negeri 2 Jember, evaluate their compliance with national education standards, and analyze the obstacles faced and solutions that can be applied in the inventory process. The method used in this research is descriptive qualitative, with data collected through field observations, intensive interviews, and documentation analysis. The results showed that most of the facilities and infrastructure in MTs. Negeri 2 Jember are available, but there are still discrepancies in the aspects of eligibility and data collection. The main obstacles found are limited competent human resources, lack of technical training, and weak asset documentation system. This study recommends strengthening the digital-based inventory system and increasing the capacity of education personnel in managing school assets. The findings are expected to be the basis for policy-making and planning for more effective and efficient infrastructure management.